Simulation of Black Hole Attack in Manet (International Journal of Engineering and Computer Science, 2016)
A Mobile Ad-Hoc Network is a collection of mobile nodes that are dynamically and arbitrarily located in such a manner that the interconnections between nodes are capable of changing on continual basis. Due to security vulnerabilities of the routing protocols, wireless ad-hoc networks are unprotected to attacks of the malicious nodes. One of these attacks is the Black Hole Attack. In this paper, we give an algorithmic approach to focus on analysing and improving the security of AODV, which is one of the popular routing protocols for MANET. Our aim is on ensuring the security against Black hole attack. The proposed solution is capable of detecting & removing Black hole node(s) in the MANET at the beginning. Also the objective of this paper is to provide a simulation study that illustrates the effects of Black hole attack on network performance.Previously the works done on MANETs focused mainly on different security threats and attacks such as Impersonation, Wormhole, Jellyfish, and Intrusion detection. Attack of black hole is required on routing protocols AODV, OLSR and TORA. And also check which protocol performs better against black hole attack. There is a need to address all these types of protocols under the attack, as well as the impacts of the attacks on the MANETs. We want to analyse Black Hole attack in MANETs using AODV, OLSR and TORA which are reactive, proactive and hybrid protocol respectively in nature.